The classical roots of the Austrian theory of capital and entrepreneurship - Meacci, Ferdinando; Ferlito, Carmelo (Springer US, 2018)
The paper deals with the continuities and discontinuities between some classical, Austrian and neo-Austrian authors with regard first to the theory of capital and then to the theory of entrepreneurship. Part I focuses on the elements of continuity between the classical and the Austrian theory of capital. These elements have been singled out by dealing first with the distinction between individual and national capital; and then with the difference between the resulting circulating-fixed capital and free-invested capital distinctions in the light, first, of the concept of roundaboutness and, then, of the method of vertical integration. Part II focuses on the elements of continuity between the Austrian theory of individual behaviour and the classical theory of national wealth. The distinctions between logical and historical time and between economics of time and economics in time are used to assess the links between the theory of capital as developed by the classics and Böhm-Bawerk, on the one hand, and the theory of entrepreneurship as developed by the neo-Austrians, on the other.